Evaluation of CSR Management "Synergy: Rising Together" to Increase SMEs Literacy - Muhammad Hafiz Nurul Haqqi (Jurnal Komunikasi Global, 2024)
PT Angkasa Pura Logistics (APLog) Public Relation divisions launched the "Synergy: Rising Together with SMEs" CSR program to improve SMEs financial management, digital marketing, and Indonesian National Standards (SNI). However, the program lacks clear success indicators and does not fully address the economic, social, and environmental pillars of CSR or the Triple Bottom Line framework. This study evaluates the programs effectiveness using Broom and Shas Four Stages of Public Relations framework: problem definition, planning, implementation, and evaluation. A qualitative descriptive approach was used, with data collected through in-depth interviews and document analysis involving SMEs participants from Bekasi, Bogor Jember, mentors, and the Public Relations Manager. Findings highlight challenges in planning, inconsistent execution, and insufficient follow-up, limiting the programs long-term impact. The study emphasizes the need for clear success indicators, practical skill-building, and adherence to CSR principles sustainability, accountability, and transparency. These improvements could enhance the program's effectiveness and align it more closely with best practices in CSR, ensuring its long-term impact and sustainability.Divisi Hubungan Masyarakat PT Angkasa Pura Logistics (APLog) meluncurkan program CSR "Synergy: Rising Together with SMEs" untuk meningkatkan manajemen keuangan UMKM, pemasaran digital, dan kepatuhan terhadap Standar Nasional Indonesia (SNI). Namun, program ini kurang memiliki indikator keberhasilan yang jelas dan tidak sepenuhnya memenuhi pilar ekonomi, sosial, dan lingkungan dalam CSR maupun kerangka Triple Bottom Line. Penelitian ini mengevaluasi efektivitas program menggunakan kerangka Four Stages of Public Relations dari Broom dan Sha: definisi masalah, perencanaan, implementasi, dan evaluasi. Pendekatan deskriptif kualitatif digunakan, dengan data dikumpulkan melalui wawancara mendalam dan analisis dokumen yang melibatkan peserta UMKM dari Bekasi, Bogor Jember, mentor, dan Manajer Hubungan Masyarakat. Temuan penelitian menunjukkan tantangan dalam perencanaan, pelaksanaan yang tidak konsisten, dan kurangnya tindak lanjut, yang membatasi dampak jangka panjang program ini. Penelitian ini menekankan pentingnya indikator keberhasilan yang jelas, pembinaan keterampilan yang praktis, dan kepatuhan terhadap prinsip-prinsip CSR seperti keberlanjutan, akuntabilitas, dan transparansi. Perbaikan tersebut dapat meningkatkan efektivitas program dan menyelaraskannya dengan praktik terbaik dalam CSR, memastikan dampak dampak jangka panjang dan keberlanjutannya.